2007
DOI: 10.1243/09544054jem769
|View full text |Cite
|
Sign up to set email alerts
|

A study of in-process waiting time on a linear walking worker assembly line

Abstract: This paper presents a study of in-process waiting times on a linear walking worker assembly line in a real buffer-constrained flowshop environment using the simulation method. The in-process waiting time can lead to production loss and in-process inventory; it can also affect the throughput time for completion of a product assembled in a sequential flowline-based manufacturing system. The aim of this research is to investigate the varying magnitude of the total in-process waiting time for individual walking wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…Simulation results of previous research (Lassalle et al 2007, Wang et al 2009) indicated that the blocking rates and in-process waiting times can, alternatively, be reduced by having more workstations than walking workers on the line. But these results were obtained based on the assumption that the work content at workstations of the line can be divisible.…”
Section: Variable (C) -Number Of Workersmentioning
confidence: 86%
See 1 more Smart Citation
“…Simulation results of previous research (Lassalle et al 2007, Wang et al 2009) indicated that the blocking rates and in-process waiting times can, alternatively, be reduced by having more workstations than walking workers on the line. But these results were obtained based on the assumption that the work content at workstations of the line can be divisible.…”
Section: Variable (C) -Number Of Workersmentioning
confidence: 86%
“…Organising the WWAL along a U-shaped layout is optimised for short walking distances for standing and Modelling and simulation of a linear walking worker assembly line considered being a random system due to the randomness of input parameters that can have a significant impact on performance of the system Lassalle et al (2007) Witness, simulation software and an external user-friendly interface for its input and output data which were managed and controlled by a series of MS Excel TM spread sheets Examination of the variable behaviour of in-process waiting time that takes place on a linear WWAL, based on two assumptions related to workers performance:…”
Section: Major System Featuresmentioning
confidence: 99%
“…& WW waiting time and travel time analysis and optimization. [35] examine the variable behavior of the in-process waiting time, while [36,37] evaluate the critical factor of in-progress waiting time and mathematically analyze the varying magnitude of production loss. & WW number of operators/stations analysis and optimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…. Equation (8) exhibits the task's assigned station and constraint (9) shows the station priority. .…”
Section: Problem Assumptions and Formulationmentioning
confidence: 99%
“…Different categories of ALBP are studied in the literature [1][2][3][4][5][6][7][8][9]. Two main categories of the problem are [1]:…”
Section: Introductionmentioning
confidence: 99%